PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL NUMBER HEAD TOGETHER BERBANTUAN MEDIA POHON PINTAR TEMA 7 KELAS IV SDN MARGOREJO 01 PATI - Khofi Anan; Mohammad Kanzunnudin; Khamdun Khamdun (PROGRES PENDIDIKAN, 2020)
This study aims to describe the improvement of teacher skills and the improvement of student’s learning outcomes in the realm of skills and knowledge by using The Number Head Together model assisted by Smart Tree Media on the 7th themes of 4th grades of SDN Margorejo 01 Pati. The material of the 7th theme of 4th grades science and Indonesian language that studied in this research are a variety of styles and non-fiction texts. This classroom action research will be conducted in 4th grades of SDN Margorejo 01 Pati with 22 students as the research subjects. The results of the research on teacher teaching skills from cycle I was 72% and in the cycle, II was an increase of 83.5%. The learning outcomes of the knowledge of Indonesian language subject from cycle I was 63.63% and in the cycle, II increased to 77.27%. While the IPA subject in the first cycle was 72.72% and the second cycle increased to 86.36%. The results of the research can be concluded that through the Number Head Together model assisted by the Smart Tree media it can improve teacher teaching skills and improve learning outcomes of fourth-grade students of SDN Margorejo 01 Pati.